International Journal of Environmental Analytical Chemistry - International Journal of Environmental Analytical Chemistry (Taylor & Francis, 2026)
International Journal of Environmental Analytical Chemistry comprises original research on all aspects of analytical work related to environmental problems. This includes analysis of organic, inorganic and radioactive pollutants in air, water, sediments and biota; and determination of harmful substances, including analytical methods for the investigation of chemical or metabolic breakdown patterns in the environment and in biological samples.
FI 0.53
Q3
Keywords: Chemistry; Acuerdos transformativos; Transformative agreements; Química analítica ambiental; Contaminantes; Calidad del agua y aire; Métodos analíticos; Monitoreo ambiental